Perseverance of Effort and Consistency of Interest: A Longitudinal Perspective - Wang, Rouhua; Shirvan, Majid Elahi; Taherian, Tahereh (Frontiers in Psychology, 2021)
The present research, enlightened by the dynamic approach to language learning, aimed to trace the co-development of English as a foreign language (EFL) learners’ perseverance of efforts (PE) and consistency of interest (CI), the two subdomains of grit, over a course time. To this aim, a factor of curves model (FCM) was employed to trace the covariance of the subdomains of L2 grit longitudinally over time; to explore how changes in PE and CI are affected by their initial states; and to what extent the variations in PE and CI are explained by the underlying global factor of L2 grit. For data collection, the L2 grit scale, recently developed by Teimouri, Plonsky and Tabandeh (2020), was used with 1384 adult EFL learners in four measurement occasions. The data were analyzed in Mplus with FCM in three steps as suggested by Wickrama, Lee, O’Neal & Lorenz (2016). The results showed that firstly, in analyzing the direction of change in PE and CI, a higher mean was estimated in the growth (the slope) than the intercept. Evidence was also found for inter-individual variation. Secondly, the covariance between the intercept and slope of each subdomain was explored and for both the results revealed a negative covariance of the slope and intercept. Thirdly, the covariance of the intercepts and the slopes of the two subdomains were positive and significant. Fourthly, the variance of the intercept and slope of each subdomain proved to be to a large extent explained by the underlying global factor of L2 grit. These findings were discussed in the light of the potential variables associated with L2 grit and its related literature.